1)4х-2=3*(х-1) 2)3*(2х+1)-4=2*(х+5) 2х-(5-3х)=4+2*(6х+3)

0 голосов
21 просмотров

1)4х-2=3*(х-1)
2)3*(2х+1)-4=2*(х+5)
2х-(5-3х)=4+2*(6х+3)


Математика (59 баллов) | 21 просмотров
0

Решите. Буду благодарна.

0

1) 4х-3х=2-3

0

1) х=-1

0

Спасибо

0

2) 6х+3-4=2х+10 6Х-2х=10+1 4х=11 х=11/4

0

3) 2х-5+3х=4+12х+6 5х-12х=10+5 -7х=15 х=-15/7

0

Спасибо большое!

Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

4x-2=3*(x-1)\\4x-2=3x-3\\x=-1

3(2x+1)-4=2(x+5)\\6x+3-4=2x+10\\4x=11\\x=2,75

2x-(5-3x)=4+2*(6x+3)\\2x-5+3x=4+12x+6\\7x=-15\\x=-\frac{15}{7}=-2\frac{1}{7}
(73.6k баллов)